From a high tower - Lackey, Mercedes (Lackey, Mercedes. Elemental masters., 2015)
"From a High Tower is newest adventure in Mercedes Lackey's Elemental Masters series, featuring a retelling of Rapunzel's not-so-happily-ever-after ending" --